SEMIOTICS STUDY OF SURAKARTA CITY GOVERNMENT TOURISM PROMOTION POSTERS AND ITS RELEVANCE AS ENGLISH MATERIAL FOR ENGLISH STUDENTS - Dian Muhammad Rifai; Sukma Shinta Yunianti (Nur Science Institute, 2023)
This study aims to analyze the description of semiotic studies from the level of signifiers and signifieds to denotative and connotative meanings originating from the tourism promotion media of the Surakarta city government. Documentation, observation, and field notes were used to collect data. The semiotic analysis method is used to analyze the research data. In conducting a semiotic analysis, the researcher used the basic theory of Roland Barthes, namely the meaning of signifiers, signifieds, denotations, and connotations on tourism promotion posters for the Surakarta City Government. By using Barthes' semiological theory of tourism promotion media in Surakarta, the results of the study show that there is a relationship between the signifier and the signified in a sign so that it clearly explains a denotative level. In addition, there is also interaction between signs in the form of denotative levels and connotative meanings so that people become interested in visiting. The results of the research obtained that every signs in the poster has their own meaning based on Rolands Barthes’theory and the form signs and their meaning can be used as the English language learning material about semantics and pragmatics in University level